2019
DOI: 10.3390/jcm9010103
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic Pattern Changes of Nucleobindin-2/Nesfatin-1 in the Brain and Intestinal Bulb of the Short Lived African Turquoise Killifish

Abstract: Nesfatin-1 (Nesf-1) was identified as an anorexigenic and well conserved molecule in rodents and fish. While tissue distribution of NUCB2 (Nucleobindin 2)/Nesf-1 is discretely known in vertebrates, reports on ontogenetic expression are scarce. Here, we examine the age-related central and peripheral expression of NUCB2/Nesf-1 in the teleost African turquoise killifish Nothobranchius furzeri, a consolidated model organism for aging research. We focused our analysis on brain areas responsible for the regulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
(98 reference statements)
0
6
0
Order By: Relevance
“…Very interestingly, Stengel and co-workers demonstrated that NUCB2/Nesf-1 expression levels in endocrine cells of gastric mucosa were 10-fold higher compared to brain levels, supporting the idea that the stomach is one of the main sites of production of circulating NUCB2/Nesf-1 [ 8 , 12 ]. Like in mammals, in teleost fish, Nesf-1 was expressed in both central and peripheral tissues, and different studies have demonstrated the highest NUCB2/Nesf-1 mRNA expression in the gastrointestinal tract [ 13 , 14 , 15 ], hypothesizing a common role of this peptide in vertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…Very interestingly, Stengel and co-workers demonstrated that NUCB2/Nesf-1 expression levels in endocrine cells of gastric mucosa were 10-fold higher compared to brain levels, supporting the idea that the stomach is one of the main sites of production of circulating NUCB2/Nesf-1 [ 8 , 12 ]. Like in mammals, in teleost fish, Nesf-1 was expressed in both central and peripheral tissues, and different studies have demonstrated the highest NUCB2/Nesf-1 mRNA expression in the gastrointestinal tract [ 13 , 14 , 15 ], hypothesizing a common role of this peptide in vertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, our group has intensively studied the annual fish Nothobranchius furzeri as a new experimental model in biology. N. furzeri has gained recognition as an animal model for aging studies, and currently, it is extensively studied in an increasing number of laboratories worldwide (Kabiljo et al, 2019;Matsui et al, 2019;Montesano et al, 2019;Fumagalli et al, 2020;Hu et al, 2020;Kelmer et al, 2020;Wang et al, 2020). These fish inhabit ephemeral pools in the semiarid bushveld of Southern Mozambique characterized by scarce and erratic precipitations and have adapted to the seasonal drying of their environment by producing desiccation-resistant eggs that can remain dormant in the dry mud for 1 and maybe more years by entering into a diapause state (Genade et al, 2005;Cellerino et al, 2016;Kim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Out of eleven papers, six are based on animal models [1][2][3][4][5][6], highlighting that these models still play a crucial role in translational medicine, even in a historical moment in which the need to find alternative methodologies is increasingly pressing.…”
mentioning
confidence: 99%
“…More specifically, the paper analyses the potential of iPSC-endothelial cells in accelerating tissue regeneration and their suitability to enter progressively more clinical trials. The most represented research field in this Special Issue is tissue morphology [1][2][3]5] followed by tissue engineering [9][10][11] and neuroscience [1][2][3], with one article intercepting both these areas of expertise [12]. This latter work reports, indeed, a method to generate a three-dimensional neuronal system composed of cortical neurons and glial cells derived from iPSCs, suitable for drug screening and disease modeling.…”
mentioning
confidence: 99%
See 1 more Smart Citation